Urales with beard and glasses, Montseny with glasses, Nettlau right with beard. Playa Rovira, in San Felice de Guixols (Gerona)
Urales with beard and glasses, Montseny with glasses, Nettlau right with beard. Playa Rovira, in San Felice de Guixols (Gerona).